2015
DOI: 10.1007/s11071-015-2226-7
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of synchronization transition processes of coupled neurons with coexisting spiking and bursting on the control parameter, initial value, and attraction domain

Abstract: As the value of a control parameter decreases, monostable bursting changes to monostable spiking via the coexistence of spiking and bursting in a Leech neuron model, and the attraction domain of the bursting decreases, while that of the coexisting spiking increases for coexisting behaviors. As the coupling strength increases, the two coupled Leech neurons with the coexisting spiking and bursting manifest transitions from non-synchronization to complete synchronization (CS) through a complex process, which is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…[15] showed diverse spatiotemporal patterns in the neuronal networks under electromagnetic induction radiation. Thus it was generally observed that the electrical activity and oscillating behaviors of biological cells are greatly reduced due to electromagnetic radiation exposure and which is consistent with biological experiments [16, 17].…”
Section: Introductionsupporting
confidence: 82%
“…[15] showed diverse spatiotemporal patterns in the neuronal networks under electromagnetic induction radiation. Thus it was generally observed that the electrical activity and oscillating behaviors of biological cells are greatly reduced due to electromagnetic radiation exposure and which is consistent with biological experiments [16, 17].…”
Section: Introductionsupporting
confidence: 82%
“…Multiple modes can be observed in neuronal activities, Gu et al . investigated the dependence of model selection on bifurcation parameter and initials selection 6 . Furthermore, Ma et al .…”
mentioning
confidence: 99%
“…Based on the wellknown neuron models, networks with different topological connections have been set to investigate the synchronization stability [36,37], pattern selection, and mode transition in collective behaviors [38][39][40][41][42][43][44][45]. Indeed, reliable and biophysical neuron model is critical and important for further investigation on neurodynamics and potential mechanism of some neuronal diseases [46].…”
Section: Complexitymentioning
confidence: 99%